Comprehensive review on biotechnological production of hyaluronic acid: status, innovation, market and applications. Issue 4 (1st April 2022) - Ucm, Ruschoni; Aem, Mera; Lhb, Zamudio; Kumar, Vinod; Taherzadeh, Mohammad J.; Garlapati, Vijay Kumar; Chandel, Anuj Kumar
ABSTRACT: The growing, existing demand for low-cost and high-quality hyaluronic acid (HA) needs an outlook of different possible production strategies from renewable resources with the reduced possibility of cross-infections. Recently, the possibility of producing HA from harmless microorganisms appeared, which offers the opportunity to make HA more economical, without raw material limitations, and environmentally friendly. HA production is mainly reported with Lancefield Streptococci A and C, particularly from S. equi and S. zooepidemicus . Various modes of fermentation such as batch, repeated batch, fed-batch, and continuous culture have been investigated to optimize HA production, particularly from S. zooepidemicus, obtaining a HA yield of 2.5 g L −1 – 7.0 g L −1 . Among the different utilized DSP approaches of HA production, recovery with cold ethanol (4°C) and cetylpyridinium chloride is the ideal strategy for lab-scale HA production. On the industrial scale, besides using isopropanol, filtration (0.22 um), ultrafiltration (100 kDa), and activated carbon absorption are employed to obtain HA of low molecular weight and additional ultrafiltration to purify HA of higher MW. Even though mature technologies have already been developed for the industrial production of HA, the projections of increased sales volume and the expansion of application possibilities require new processes to obtain HA with higher productivity, purity, and specific molecular weights. In this review, we have put forth the progress of HA technological research by discussing the microbial biosynthetic aspects, fermentation and downstream strategies, industrial-scale scenarios of HA, and the prospects of HA production to meet the current and ongoing market demands. Graphical Abstract: uf0001